2019
DOI: 10.1186/s13148-019-0700-7
|View full text |Cite
|
Sign up to set email alerts
|

Peptides as epigenetic modulators: therapeutic implications

Abstract: Peptides originating from different sources (endogenous, food derived, environmental, and synthetic) are able to influence different aspects of epigenetic regulation. Endogenous short peptides, resulting from proteolytic cleavage of proteins or upon translation of non-annotated out of frame transcripts, can block DNA methylation and hereby regulate gene expression. Peptides entering the body by digestion of food-related proteins can modulate DNA methylation and/or histone acetylation while environmental peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 169 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that plant AMPs can play a role as epigenetic modulators in cancer cells ( Arceo-Martínez et al, 2018 ; Janssens et al, 2019 ). To evaluate whether the cytotoxic effect of PaDef was related to epigenetic modifications, we explored some epigenetic marks of Histone 3 (H3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that plant AMPs can play a role as epigenetic modulators in cancer cells ( Arceo-Martínez et al, 2018 ; Janssens et al, 2019 ). To evaluate whether the cytotoxic effect of PaDef was related to epigenetic modifications, we explored some epigenetic marks of Histone 3 (H3).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, some AMPs are not toxic to normal mammalian cells and have a broad spectrum of cytotoxic activity on tumor cells. Also, it has been described the epigenetic modulation of AMPs related to anticancer activities, as is the case of lunasin, a peptide derived from soy that inhibits the acetylation of Histone 3 and 4 ( Wan et al, 2017 ; Janssens et al, 2019 ). This fact increases the relevance of the study of AMP as an attractive source of new therapies against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, including food, microbiota, physical activities, and environmental pollutants can largely influence epigenetic changes. Epigenetic modifications can also affect one another by adding extra layers of epigenetic regulation [ 53 ]. Epigenetic processes being reversible and labile, are regulated by different signature proteins or molecules.…”
Section: Epigenetic Basis Of Neural Plasticitymentioning
confidence: 99%
“…The third and last class, i.e., the epigenetic modulators, are tissues-specific proteins vital to normal cellular functions as they lead the cell and tissue differentiation mechanisms. They transmit environmental signals to the epigenetic modifiers [151][152][153][154] DNA methylation DNA methylation is one of commonest studied and well-characterized among the changes. The process involves transferring a methyl group to position 5′ of the pyrimidine-cytosine of 5′-CpG-3′-rich DNA regions called CpG islands: a palindromic set of cytosine-phosphate-guanine dinucleotides found in the promoter region and other genomic regions.…”
Section: Epigenetic Modulators Modifiers and Mediatorsmentioning
confidence: 99%